Cognitive functions and sense of coherence in patients with carotid artery stenosis—Preliminary report - Piegza, Magdalena; Dębski, Paweł; Bujak, Kamil; Jaworska, Izabela; Gorczyca, Piotr; Pudlo, Robert; Żerdziński, Maciej; Piegza, Jacek (Frontiers in Psychiatry, 2023)
Background: There is scarcely any data in the available literature on the relationship between sense of coherence (SOC) and cognitive functioning, and no information on the relationship between SOC and cognitive parameters in patients with carotid atherosclerosis. Aim: The aim of this paper was to determine the relationship of SOC measured prior to carotid artery stenting (CAS) with neurocognitive functioning in patients with carotid atherosclerosis 12 months after CAS.Methods: 35 patients with carotid atherosclerosis completed the SOC-29 Orientation to Life Questionnaire (SOC-29) and completed a cognitive test battery twice, i.e. before (baseline -T1) and 12 months after stent implantation (follow-up -T2). Selected cognitive functions such as memory, attention, perception, visuospatial and executive functions and non-verbal fluency were assessed. Results: One year after the procedure, patients with a higher SOC and sense of manageability present better performance in visual memory. Higher SOC and sense of meaningfulness are positively related to the speed of understanding the changing rules of card sorting (WCST). Conclusions: Higher overall SOC and a component of sense of meaningfulness and manageability may be related to better cognitive functioning one year after the procedure.